(untitled) (Global Journal of Management and Business Research, 2019)
Insurance industry is recorded high growth rate in Sri Lanka in the recent years. The delivery of high-quality service is the vital to success in service industries. Customers are likely to choose insurance company that has high quality of service such as provide complete information about the product and services, well-known and positive corporate image, handle the complaints. Service quality is a recent and more dynamic decisive issue in the marketing thought. The population was the customer who has life insurance policies in the top five insurance companies which are lapsed within one year and structured questionnaire is used as a major method to collect primary data. The special case is that population sample was selected from all 25 districts and 200 respondents are selected as the sample out of the total population. This paper examines the impact of Service Quality of the life insurance companies on their customer satisfaction. The SERVQUAL instrument is selected to measure service quality. The results of the study confirms that tangibility, responsiveness, assurance and empathy have a moderate positive influence on customer satisfaction and even though reliability has negative relationship, it impacts on customer satisfaction in the insurance industry. Further the researcher identified that assurance was the most important factor. It has considerable impact on customer satisfaction in Insurance industry.